South–South relations under world market capitalism: the state and the elusive promise of national development in the China–Ecuador resource-development nexus. Issue 5 (3rd September 2017) - Gonzalez-Vicente, Ruben
ABSTRACT: Optimistic commentators welcome 'the rise of the South' as a phenomenon that will transform geopolitical architectures and development thought. This essay situates this alleged rise and 'South–South relations' within world market capitalism and discusses their liberating potential with a case study of Chinese mining investment in Ecuador. Despite the ostensibly differing approaches to development embodied in the Chinese and Ecuadorian alternatives to neoliberalism, the Mirador project reveals eerily familiar outcomes, dominated by visions of national modernization and business-state alliances that reproduce market inequalities and postcolonial exclusions. While the Mirador project grants significant economic clout to pursue development through redistributive means, it also attests to the role of the state in opening new market frontiers and securing conditions for transnational capital accumulation. I argue that in this context and similar ones, it is problematic to project the attributes of the South as a symbol of struggle for emancipation on to the nation-state. Although the South remains a useful concept, it should be understood as a space made up by those who are subject to diverse forms of oppression in the name of globalization and national development – a space that is reshaped by the works of the state in multiple and often contradictory ways.